PENGARUH KINERJA KEUANGAN TERHADAP DEVIATION ACTUAL GROWT RATE DARI SUSTAINABLE GROWTH RATE - Barbara Gunawan; Dian Puteri Leonnita (Jurnal Riset AKuntansi dan Bisnis)
The purpose of this research wa to analyze the influence of financial performance to the deviation of  actual growth rate of sustainable growth rate with the financial performance includes of profitability, liquidity, leverage, and asset management. This reseacrh uses secondary data are derived of the financial statements companies listed on the Indonesian Stock Exchange and Kuala Lumpur Stock Exchange during 2013-3014. This research used a purposive sampling method and obtained as much as 186 companies consist of 72 companies from Indonesia and 76 companies from Malaysia. The method of analysis in this study using multiple linear regression with SPSS 20.0.  The results showed that return on asset (ROA), current ratio (CR), debt to equity ratio (DER), and inventory turnover (IT) together have a significant effect on the deviation actual growth rate from sustainable growth rate in Indonesia but haven’t a significant effect in Malaysia. The partial test result showed that CR has negative significant effect to dependent variable in Indonesia but hasn’t significant effect to dependent variable in Malaysia. DER has positive significant effect to dependent variable in Indonesia but hasn’t significant effect to dependent variable in Malaysia. IT has negative significant effect to dependent variable in Malaysia but hasn’t significant effect to dependent variable in Indonesia. ROA has no significant effect to variable dependen in Indonesia and Malaysia.